Penggunaan Media Film sebagai Sarana Pembelajaran Etika Akuntan: Implementasi pada Mata Kuliah Audit - Padma Adriana Sari; Kurnia Ekasari; Rosy Aprieza Puspita Zandra (Organum: Jurnal Saintifik Manajemen dan Akuntansi, 2020)
Teaching ethics to accounting students is a challenge for lecturers. Lack of knowledge on how to teach ethics and limited references to ethics teaching materials are examples of obstacles to teaching ethics. The film has been an exciting learning resource in accounting courses, which is a fun way to learn and full of value. This study is a preexperimental study to determine the effectiveness of using film media to convey ethical material to students majoring in Accounting, Politeknik Negeri Malang. The method used in this study is descriptive qualitative. Based on the results of this experiment, 32 students stated that there were moral values that were learned from watching films. In contrast, 17 people indicated that they had learned other things such as cases of economic crisis and the application of the material in class to real life. Based on these results, films could be used as an alternative to teaching ethics to accounting students. This study offered a reference for accounting lecturers the ways to use film in accounting classes and samples of discussion and assignments in using film as a teaching resource. The result of this study could be a reference in renewing the curriculum to insert film as a learning resource, also to consider other learning resources.